'All elderly people have important service needs': a study of discourses on older people in parliamentary discussions in Finland. Issue 1 (4th September 2014) - PULKKI, JUTTA; TYNKKYNEN, LIINA-KAISA
ABSTRACT: This study examines discursive constructions of older people by analysing the talk of members of parliament in parliamentary discussions in Finland. While the perceptions of older people that are constructed in various public and private arenas have been relatively widely examined, the talk of political decision makers has not been studied to any large extent. However, decision makers' understandings of older people are likely to influence the ways in which service systems are developed and services organised for older people. The parliamentary discussions examined in this study were related to the process of enacting legislation to secure services for older people. Using discourse analysis, three ways of constructing older people – as 'the dependent', 'the active' and 'the deserving' – are identified. Although the results are to some extent in accordance with previous findings, indicating that older people are constructed as either totally dependent and passive or extremely active, this study also breaks this dichotomous view and highlights the overlap between those constructions. Nonetheless, the picture of older people remains fairly one-dimensional. There was an absence of recognition of diversity among older people, which might inhibit the development of a customer-oriented service system.